No evidence for altered muscle mitochondrial function in Parkinson's disease. Issue 5 (May 1993) - Anderson, J J; Bravi, D; Ferrari, R; Davis, T L; Baronti, F; Chase, T N; Dagani, F
Abstract : Recent reports indicate that reductions in mitochondrial respiratory chain function occur in substantia nigra, platelets, and muscle from patients with Parkinson's disease. To confirm and further characterise the presence of a generally distributed mitochondrial defect, mitochondrial metabolism was evaluated in muscle obtained from subjects with Parkinson's disease and from normal controls. Oxygen consumption rates in muscle mitochondria represented by complex I, complexes II-III, or complex IV did not differ between the two groups. Likewise, activities of rotenone sensitive NADH cytochrome c reductase, succinate cytochrome c reductase, or cytochrome oxidase in muscle mitochondria were not significantly different between Parkinsonian and control subjects. These findings fail to provide support for a generalised defect in mitochondrial function in Parkinson's disease but do not exclude an abnormality in respiratory function confined to the substantia nigra.